Are Resilience, and Spirituality Related to Marital Peace? Explorations in Silver Age Couples - Afita Nur Hayati,; Sai Handari,; Firda Karwina Awaliah,; Aulia Rahmatul Azizah,; Ikrima Bestari Agsal Kurniad, (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
This study aimed to determine the relationship between resilience and spirituality with marital peace in couples of silver or twenty-five years of marriage age in East Kalimantan. The approach in this study uses quantitative-qualitative methods with regression and narrative data analysis methods. Respondents in this study were married couples who were in the Qaryah Tayyibah community totaling 31 people. The results of the quantitative analysis show that resilience and spirituality can explain and influence marital peace by less than 1%. This means that the other 99% is influenced by different factors. In the F test, the results show that resilience and spirituality do not affect marital peace. The t-test is negative, indicating that the resilience variable does not affect marital peace, as well as the spirituality variable. Results of the narrative analysis of qualitative data from focus group discussions (FGDs) reveal that the resilience variable has a relationship with spirituality but no relationship with the marital peace variable. This study can provide an empirical contribution, namely the support of spirituality variables on marital resilience and effective communication, social support, and emotional intimacy to maintain a healthy relationship despite facing challenges.